Pengaruh Vegetasi pada Tipe Habitat Monokultur Kopi, Agroforestri berbasis Kopi, dan Hutan terhadap Keanekaragaman Jenis Burung di Blok Pemanfaatan, KPH Batutegi - Iswandaru, Dian; Pardede, Lusiana Br.; Fitriana, Yulia Rahma; Darmawan, Arief; Kaskoyo, Hari; Wulandari, Christine; Herwanti, Susni; Novriyanti, Novriyanti; Febryano, Indra Gumay; Safe’i, Rahmat; Dewi, Bainah Sari (Universitas Pattimura, 2025)
Bird habitat use is closely linked to survival, reflecting reciprocal interactions between avifauna and vegetation structure within managed landscapes. Coffee monoculture, coffee-based agroforestry, and community-managed forests represent land-use systems with varying capacities to support bird communities in the Utilization Block of the Batutegi Forest Management Unit (KPH Batutegi), Lampung, Indonesia. This study aimed to assess bird species diversity, species similarity, feeding guild composition, and the influence of vegetation and environmental variables across these habitat types. Bird surveys were conducted using the point count method, complemented by quantitative analyses of vegetation structure and environmental factors. Results indicate that the highest bird species diversity occurred in forest habitats (H′ = 2.490), while the greatest species similarity was observed between forest and coffee monoculture habitats (J = 0.464). Across all land-cover types, bird communities were dominated by insectivorous feeding guilds, accounting for 55% in coffee-based agroforestry, 44% in forest habitats, and 42% in coffee monoculture systems. Multivariate regression analyses revealed that vegetation attributes (diversity and density) and environmental variables (altitude, slope, temperature, and humidity) did not exert a significant influence on bird diversity. This pattern is attributed to pervasive anthropogenic pressures, including land-use homogenization, forest modification, and ongoing human disturbance. These findings underscore the need for systematic monitoring and improved land-management practices to mitigate anthropogenic impacts and enhance the ecological function of coffee-based landscapes and forest habitats in supporting avian biodiversity.